Framing Analysis of Online Sexual Harassment News Against Online Motorcycle Bikes by Online Media Detik.com and Viva.co.id - Hanifan Ma'ruf (Jurnal Komunikasi, 2023)
The issue of sexual harassment through online or online networking is a topic that is being seriously highlighted by various parties and comes to the fore in the term Online Gender-Based Violence (OGBV). This research focuses on the perspective of mass media reporting in bringing up a phenomenon of online sexual harassment to the public. Specifically, the study discusses the phenomenon of online sexual harassment cases that are actually experienced by men, namely Online Motorcycle Taxi (Ojol) drivers. This fact was analyzed textually using Robert Entman's model framing analysis method of two news manuscripts from two different online media, namely Viva.co.id and Detik.com. This research with a qualitative descriptive approach aims to find out the framing efforts and construction of reality made by the two online media around online sexual harassment cases against Ojol drivers through their respective news texts. The results of the study concluded that the two news stories on the online media had tried to insist on participation to the managers of the application service to provide protection to Ojol drivers which showed the partiality of the media to the victims. Based on the theory of media setting agendas, both news stories have included the agenda of the media and the agenda of the audience, but have not given a significant portion to the authorities as a policy agenda to come up with a solution to this problem of online sexual harassment